Historical Analysis On Fundamentalism Movement Of High School Students In Kediri City East Java - Anis Humaidi (Didaktika Religia, 2020)
This article aims to reveal the historical roots and patterns of the fundamentalism movement among students in the City of Kediri. This article is based on the field a qualitative case study. Fundamentalism is a movement that is very close to radicalism. However, the spread of fundamentalism was also found in educational institutions. This article concludes that after going through a series of in-depth studies, this article concludes that historically it cannot be found when this fundamentalism movement began to spread in State Senior High School 1 (SMAN) and State Senior High School 2 (SMAN) Kediri. What is found is that there are Islamic study activities that have allegedly been around since the school began operating. Both in SMAN 1 and SMAN 2 Kediri, no definitive clue was given as to when the spread of the religious fundamentalism movement began. The fundamentalist movement patterns in SMAN 1 and SMAN 2 Kediri City have similarities, namely through Islamic study activities. In SMAN 1, Kediri City, there are SKI activities. Meanwhile, at SMAN 2 Kediri, there were a number of activities, such as PETUAH (Saturday Sunday Pesantren) BAO, MabÄ«t (the night of devotion), and Aqidah. There is also the At-Tholab association (a collection of several schools). Some of these activities are a forum for the spread of Islamic religious fundamentalism, which is claimed to teach Islamic teaching in accordance with the Quran and Hads